Unplanned 30-day readmission rates after plastic and reconstructive surgery procedures: a systematic review and meta-analysis - Tapking, Christian; Boson, Alexis L.; Rontoyanni, Victoria G.; Kowalewski, Karl-Friedrich; Hundeshagen, Gabriel; Haug, Valentin; Houschyar, Khosrow S.; Popp, Daniel; Branski, Ludwik K. (European journal of plastic surgery, 2020)
Identifying risk factors for unplanned hospital readmission is beneficial in terms of costs and utilization of resources. This systematic review aimed to identify and compare the rates and common reasons for readmission following reconstructive and esthetic surgery.